India’s Collaboration with Latin America as Reflected in Co-authored Papers - Gupta, B.M.; Singh, Mohinder (DESIDOC Journal of Library & Information Technology, 2003)
India’s relations with the Latin American countries have been traditionally friendly and interaction with them is close both at bilateral and multilateral level. India’s collaboration with Latin American countries has resulted in different kinds of outputs, including joint publications, technology development, technology transfer, improvised products and processes. The joint research output emanating out of research collaboration is an important source of information for mapping India’s collaboration with Latin America, and its impact on different fields. This paper attempts to study the research collaboration of India with Latin America, with the following objectives: (i) To study the nature of Indian collaboration with Latin American countries in S&T, as reflected in co-authored research papers, (ii) To identify the specific subject areas of Indian collaboration with Latin America, (iii) To study the impact of Indian collaborative research with Latin America in different fields, and (iv) To identify the major Indian institutions involved in this collaborative research with institutions in Latin America. http://dx.doi.org/10.14429/dbit.24.3.3626